Release of minerals in groundnut haulm based complete diets supplemented with organic and inorganic mineral sources by in sacco method in steers - RANI, K SUDHA; RAMANA, J V; DEVASENA, B; RAVI, A; REDDY, P SUDHAKARA (The Indian Journal of Animal Sciences, 2015)
The study was carried out to evaluate the effect of organic and inorganic mineral supplementation to groundnut haulm (GNH) based complete diets on mineral release by in sacco method. A basal complete diet was prepared with GNH and concentrate mixture (8% maize, 10% soybean meal, 21.5% deoiled rice bran and 0.5% salt) in 60:40 ratio. The basal diet was treated as control (T1) and 3 more diets were prepared by supplementing basal diet with commercial mineral mixture (T2), inorganic mineral supplements (T3) and organic mineral supplements (T4). The commercial mineral mixture was added at the rate of 1.5% in T2/sub> diet by adjusting the deoiled rice bran to 20%. The inorganic mineral supplements were added at the rate of 26.4g (8.3g ZnSO4, 4.0g CuSO4 and 14.0 g MnSO4) in the T3 diet. The organic mineral supplements were added at the rate of 72g (12g Zn-P, 10 g Cu-P and 50g Mn-P) in the T4 diet. The in sacco mineral release of Cu, Mn and Zn from experimental diets showed that the disappearance % was higher in commercial mineral mixture supplemented diet followed by organic mineral supplemented diet, and then inorganic mineral supplemented diet. The in sacco copper, manganese and zinc release from feed ingredients revealed that copper disappearance (%) was higher in all the feed ingredients followed by Mn and Zn. The NDF degradability also increased with increase in incubation time. A correlation was drawn between in sacco mineral release and NDF degradability of the treatment diets. Significant positive correlation was observed between the NDF degradability and mineral release in the rumen. It can be concluded that the organic mineral supplements were better bioavailable than the inorganic mineral supplements.